The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ijms22168945
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics as a Tool to Elucidate the Sensory, Nutritional and Safety Quality of Wheat Bread—A Review

Abstract: Wheat (Triticum aestivum) is one of the most extensively cultivated and used staple crops in human nutrition, while wheat bread is annually consumed in more than nine billion kilograms over the world. Consumers’ purchase decisions on wheat bread are largely influenced by its nutritional and sensorial characteristics. In the last decades, metabolomics is considered an effective tool for elucidating the information on metabolites; however, the deep investigations on metabolites still remain a difficult and longt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 98 publications
0
6
0
Order By: Relevance
“…It is worth noting that recently, more attention is being paid to γ-aminobutyric acid which is formed via the enzymatic reaction of glutamic acid with several important roles in human metabolism such as hypotensive, diuretic, neurotransmitter, and inhibitor of leukemia cell proliferation [ 54 , 55 ]. Furthermore, in all samples, Val, Ile, and Leu were identified and claimed by the literature to have an essential role in human muscle damage recovery, fatigue, and soreness due to physical effort.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that recently, more attention is being paid to γ-aminobutyric acid which is formed via the enzymatic reaction of glutamic acid with several important roles in human metabolism such as hypotensive, diuretic, neurotransmitter, and inhibitor of leukemia cell proliferation [ 54 , 55 ]. Furthermore, in all samples, Val, Ile, and Leu were identified and claimed by the literature to have an essential role in human muscle damage recovery, fatigue, and soreness due to physical effort.…”
Section: Discussionmentioning
confidence: 99%
“…HIT has not used to evaluate the impact of such biochemical changes on wheat quality and should be the subject of in-depth study, potentially in combination with other techniques. By providing valuable insights into the biochemical pathways and compounds that influence wheat growth, development, and quality, metabolomics involving small molecules or metabolites within a biological system can be used as a powerful analytical approach for wheat quality analysis from a microscopic level ( Saia et al, 2019 , Păucean et al, 2021 ). Metabolomics and HIT are two distinct techniques and provide complementary information about different aspects of wheat samples.…”
Section: Application Of Hit In Wheat Quality Evaluationmentioning
confidence: 99%
“…In order to explore the selectivity of 1-6 for cancer cell lines, we tested their cytotoxicity toward normal fibroblasts, calculated IC50 values and selectivity index, which is the most commonly reported as a simple ratio of IC50 calculated for healthy and cancer cells [47] . Analysis of the selectivity index revealed that all tested complexes had a lower selectivity index compared to cisplatin (Table 7).…”
Section: In Vitro Studiesmentioning
confidence: 99%